FMR1 genotype with autoimmunity-associated polycystic ovary-like phenotype and decreased pregnancy chance. - Norbert Gleicher (Public Library of Science (PLoS), 2010)
The FMR1 gene partially appears to control ovarian reserve, with a specific ovarian sub-genotype statistically associated with a polycystic ovary (PCO)- like phenotype. Some forms of PCO have been associated with autoimmunity. We, therefore, investigated in multiple regression analyses associations of ovary-specific FMR1 genotypes with autoimmunity and pregnancy chances (with in vitro fertilization, IVF) in 339 consecutive infertile women (455 IVF cycles), 75 with PCO-like phenotype, adjusted for age, race/ethnicity, medication dosage and number of oocytes retrieved. Patients included 183 (54.0%) with normal (norm) and 156 (46%) with heterozygous (het) FMR1 genotypes; 133 (39.2%) demonstrated laboratory evidence of autoimmunity: 51.1% of het-norm/low, 38.3% of norm and 24.2% het-norm/high genotype and sub-genotypes demonstrated autoimmunity (p=0.003). Prevalence of autoimmunity increased further in PCO-like phenotype patients with het-norm/low genotype (83.3%), remained unchanged with norm (34.0%) and decreased in het-norm/high women (10.0%; P<0.0001). Pregnancy rates were significantly higher with norm (38.6%) than het-norm/low (22.2%, p=0.001). FMR1 sub-genotype het-norm/low is strongly associated with autoimmunity and decreased pregnancy chances in IVF, reaffirming the importance of the distal long arm of the X chromosome (FMR1 maps at Xq27.3) for autoimmunity, ovarian function and, likely, pregnancy chance with IVF.